CAZ Composite Photocatalysts for H2 Production and Degradation under Visible Light - Zhang, Jinfeng (Langmuir : the ACS journal of surfaces and colloids, 2024)
g-C3N4/Ag-ZnO (CAZ) composite photocatalysts were synthesized successfully by the hydrothermal method. The photocatalytic performance of photocatalysts was assessed through experiments measuring both hydrogen (H2) production and the degradation of methylene blue (MB). The H2 production rate of 60% CAZ reached 2.450 mmol·g-1·h-1, which was 8.5 times that of g-C3N4. 25% CAZ degraded 99.14% of MB dye within 40 min, and its degradation rate constant was 12.4 times that of g-C3N4. CAZ composite photocatalysts have good synergistic properties in degradation and hydrogen production and exhibit better photocatalytic performance. A Z-scheme photocatalytic system mechanism of CAZ has been proposed for the enhanced H2 production and photocatalytic degradation rate